KONTRIBUSI FUNGSI KELUARGA TERHADAP PERILAKU REMAJA MEROKOK DI SMA/SMK KECAMATAN GOMBONG, KEBUMEN JAWA TENGAH. - marsito -; junaiti sahar; mustikasari - (Jurnal Ilmiah Kesehatan Keperawatan, 2009)
Teenagers have big influence on clean and health lifestyles such as no smoking lifestyle. That is why; the family function has an important role on controlling the smoking behavior of the teenagers. This is a descriptive correlation research with the cross Sectional approach to find out the family function influence that divided into 5 family functions; affective, social function, economic function, reproductive function, and health function correlated with the smoking behavior of SMA/SMK  students in Gombong, Kebumen Regency, Central Java. There are 220 teenagers as the samples in this research. They are still in Senior High School (Vocational High School/SMK and General High School/SMA) and they are smokers. The sampling technique was done by using the Cluster Random Sampling. The data analyses used were univariate, bivariate, with Chi Square test and multivariate with the regression logistic test. The research found that the family function influenced the smoking behavior of the students in SMK/SMA in Gombong are social function (p value =0.000), economic function (p value =0.003), reproductive function (p value =0.004) and affective function (p value =0.008). Meanwhile the most dominant family functions variable that influenced the smoking behavior of SMK/SMA students were social and family economic functions. Because of this reason, it is necessary for the parents or family to have a strong commitment to apply their function as the family to control their teenage children and they can also consider their teenage children development characteristics. Community Nurse has a role on giving suggestion to the parents so that they can do their exact function as the family and give the right and needed information for their teenage children appropriate with their children development stages.   Keywords; family function, teenage smokers.